Economic feasibility of calcium looping under uncertainty - Hanak, Dawid P.; Manovic, Vasilije (Elsevier, 2017)
An emerging calcium looping process has been shown to be a promising alternative to solvent scrubbing, which is regarded as the most mature CO2 capture technology. Its retrofits to coal-fired power plants have the potential to reduce both energy and economic penalties associated with the mature CO2 capture technologies. However, these conclusions have been made based on the deterministic outputs of the economic models that have not considered uncertainties in the model inputs. Therefore, this study incorporates a stochastic approach into the economic analysis of the retrofit of such emerging CO2 capture technology to the coal-fired power plant. The stochastic analysis revealed that levelised cost of electricity (LCOE) and specific total capital requirement were highly affected by the uncertainty in the input variables to the process and economic models. The most probable values for these key economic performance indicators were shown to fall between 75 and 115 €/MWelh, and 2100 and 2300 €/kWel,gross, respectively. Interestingly, the most probable LCOE values for the coal-fired power plant will fall between 50 and 150 €/MWelh. This indicated that the calcium looping retrofit scenario can become economically favoured, mainly due to the high economic penalties incurred by unabated coal-fired power plant associated with carbon tax. Importantly, the outputs of the stochastic economic assessment aligned well with the deterministic results reported in the literature. As the latter were generated using different sets of assumptions regarding the process and economic models, the stochastic approach to the economic assessment can minimise the impact of the model assumptions on estimates of the key economic parameters. Moreover, by indicating the probability of particular outputs, as well as ranking the model input variables according to their influence on the key economic performance, such analysis would allow making more insightful decisions regarding further funding and development of the calcium looping process. Finally, use of the stochastic approach in the economic feasibility assessment enables a more profound and reliable comparison of the different calcium looping retrofit configurations, as well as benchmarking different CO2 capture technologies.
Keywords: Uncertainty; Probabilistic analysis; Coal-fired power plant; Process modelling and simulation; Techno-economic analysis; Calcium looping